Sorting sexualities: Expertise and the politics of legal classification - Vogler, S. (Stefan) (Chicago : The University of Chicago Press, 2021)
c
Introduction -- Kissing cousins : queerness, crime, and knowing -- Seeing sexuality like a state -- Forensic psychology, complicit expertise, and the legitimation of law -- Insurgent expertise and the hybrid network of LGBTQ asylum -- Asylum seekers and signs of queerness -- Sex offenders and the detection of deviance -- Queer subjects and the construction of risky countries -- Sexual predators and the constitution of dangerous individuals -- Conclusion : sexuality, science, and citizenship in the twenty-first century.
Includes bibliographical references and index.
Keywords: Sex and law -- United States; Sexual minorities -- Classification -- Social aspects -- United States; Gay political refugees -- United States; Sex offenders -- United States; Classification -- Social aspects -- United States; Evidence, Expert -- United States; Justice, Administration of -- United States; Gender and Sexuality